New records of Rhagomys rufescens (Rodentia: Sigmodontinae) in the Atlantic forest of Brazil - Steiner-Souza, Francisco; Cordeiro-Estrela, Pedro; Percequillo, Alexandre Reis; Testoni, André Filipe; Althoff, Sérgio Luiz (Zootaxa, 2008)
Since it was trapped in the XIX th century, Rhagomys rufescens has been considered a rare endangered sigmodontine rodent and an endemic species of the Atlantic forest. Only a handful of vouchers of this taxon were known by Thomas, 1886. Recently, eight new individuals were collected, providing new geographical, morphological and phylogenetic (based on molecular evidence) information on this species. In the present work we report the southernmost occurrence record for R. rufescens at Indaial, Santa Catarina State, with the largest collected series of this species, the northernmost occurrence record at Santa Teresa, Espírito Santo State, and new records from Poços de Caldas, Minas Gerais State, from Ibiúna and Ribeirão Grande, São Paulo State.